The Evil Genius of Suárez: Suárez and Descartes - Baciero Ruiz, Francisco T. (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
Cartesian philosophy has traditionally been considered as an almost absolute beginning in the history of philosophy. Nevertheless, the well-known hypotheses of the «evil genius» and «deceiving God», fundamental pieces in the artifice of «methodical doubt» in Metaphysical Meditations, can be found in Suárez’s Metaphysical Disputation 9 (the only mention of Suárez in the entire work of Descartes, specifically in the «Responses» to the Meditations). It seems quite clear, considering the correspondence between Descartes and Mersenne, as well as his doctrine about the sources of error, that Descartes borrowed both fictions directly from Suárez.
Keywords: modern philosophy; theory of knowledge; second Spanish scholastic; Jesuits; Suárez; Descartes